PENGARUH ORIENTASI PASAR, ORIENTASI KEWIRAUSAHAAN, DAN KEUNGGULAN BERSAING TERHADAP KINERJA PEMASARAN UMKM (Studi Pada Pelaku Usaha Kuliner Kecamatan Bandar Sribhawono, Kabupaten Lampung Timur) - Siti Bilqis Sulaiman; Hartono Hartono; Fanny Saptiani (Jurnal Kompetitif Bisnis, 2023)
This study aims to determine the influence of market orientation, entrepreneurial orientation and competitive advantage on the marketing performance of SMEs. This type of research uses explanatory research with a quantitative approach. The population of this research is culinary businessmen in the Bandar Sribhawono sub-district. The sampling technique in this study used the nonprobability sampling method with a sample of 40 respondents. Analysis of the research data used multiple linear regression analysis using the SPSS 24 application. Test the hypothesis using the t test and F test. The t results show that the variables market orientation, entrepreneurial orientation, and competitive advantage partially have a positive and significant effect on the marketing performance of MSMEs. The results of the F test show that marketing performance is significantly and positively influenced simultaneously by market orientation, entrepreneurial orientation, and competitive advantage.